2004
DOI: 10.1007/s00299-004-0797-8
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of Campanula carpatica: factors affecting transformation and regeneration of transgenic shoots

Abstract: An efficient transformation system for Campanula carpatica was developed using Agrobacterium tumefaciens strains LBA4404 (harbouring the plasmid pBI121), and AGL0 (harbouring the plasmid pBEO210). This is the first report on the transformation of C. carpatica. Various factors affecting the transformation efficiency and subsequent regeneration were identified. The age of seedlings from which the explants for transformation studies were taken, and the growth conditions under which the seedlings were grown had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Prior incubation in the dark is very important process for dedifferentiation and differentiation of P. occidentalis. Incubation in the dark has been reported to increase shoot regeneration in various plant species, such as blueberry (Billings et al 1988), pear (Chevreau et al 1989), apple (Fasolo et al 1989), campanula (Sriskandarajah et al 2004), watermelon (Compton 1999), Zhanhua winter jujube (Gu and Zhang 2005) and quince (Baker and Bhatia 1993). Our results indicated that an incubation period of 7 days in the dark is optimal for shoot regeneration of P. occidentalis (data not presented).…”
Section: Plant Regeneration From Leaf Explantscontrasting
confidence: 69%
“…Prior incubation in the dark is very important process for dedifferentiation and differentiation of P. occidentalis. Incubation in the dark has been reported to increase shoot regeneration in various plant species, such as blueberry (Billings et al 1988), pear (Chevreau et al 1989), apple (Fasolo et al 1989), campanula (Sriskandarajah et al 2004), watermelon (Compton 1999), Zhanhua winter jujube (Gu and Zhang 2005) and quince (Baker and Bhatia 1993). Our results indicated that an incubation period of 7 days in the dark is optimal for shoot regeneration of P. occidentalis (data not presented).…”
Section: Plant Regeneration From Leaf Explantscontrasting
confidence: 69%
“…b (Sriskandarajah et al, 2004). The adventitious shoot regeneration of Zhanhua winter jujube (Z. jujuba) was maximal (76.2% of leaf explants producing shoots) when explants had been incubated in the dark for 20 d (Gu and Zhang, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of explants also plays a pivotal role in determining transformation efficiency. Young and tender explants are typically favored for infestation, as reported in several studies (Hadfi and Batschauer, 1994;Liu et al, 2013;Sriskandarajah et al, 2004). In potato, leaf and internode explants from various cultivars were infected with Agrobacterium tumefaciens strain LBA4404, yielding a transformation efficiency of 22% for internode explants and 15% for leaf discs in the Lady Olympia cultivar (Bakhsh, 2020).…”
Section: The Influence Of Varieties and Leaf Age On Hairy Root Format...mentioning
confidence: 89%